Post-disaster recovery and support in Japan - Kawai, K (Refugee Studies Centre, University of Oxford, 2014)
As a locally based faith-based organisation, there were several aspects that enabled Soka Gakkai to contribute effectively to the relief effort following the March 2011 earthquake and tsunami in Japan, responding to both physical and psychological needs.